The Role of Bank Guarantee As Collateral in The Implementation of Work on Projects At PT Hutama Karya (Persero) EPC Division (Study on The Muara Tawar 2 X 650 MW Power Plant Project) - Achmad Fikri; Suparji Suparji; Suartini Suartini (Publikasi Indonesia, 2024)
Large projects such as power plants require guarantees for the implementation of the work to ensure the project's smooth running. A Bank guarantee is commonly used in these large projects to ensure contract fulfillment and good performance. This research aims to evaluate bank guarantees' role in projects such as the 2 x 650 MW Muara Tawar Power Plant run by PT Hutama Karya (Persero) EPC Division. This research uses qualitative research methods. Data collection techniques in this study include literature studies and interviews. Data analysis techniques used in this study include data reduction, data presentation, and conclusion drawing. The results showed that bank guarantees are essential in implementing work on projects at PT Hutama Karya (Persero) EPC Division. Bank guarantees can be used to guarantee various things, such as quality of work, timely completion, and payments to third parties. Bank guarantees have various benefits in the implementation of work on projects at PT Hutama Karya (Persero) EPC Division, including increasing the employer's trust in service providers, increasing the certainty of work implementation, and increasing efficiency in the work implementation process.